2015
DOI: 10.1038/nature15378
|View full text |Cite
|
Sign up to set email alerts
|

A sexually dimorphic hypothalamic circuit controls maternal care and oxytocin secretion

Abstract: It is commonly assumed, but has rarely been demonstrated, that sex differences in behaviour arise from sexual dimorphism in the underlying neural circuits. Parental care is a complex stereotypic behaviour towards offspring that is shared by numerous species. Mice display profound sex differences in offspring-directed behaviours. At their first encounter, virgin females behave maternally towards alien pups while males will usually ignore the pups or attack them. Here we show that tyrosine hydroxylase (TH)-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(246 citation statements)
references
References 34 publications
14
229
1
2
Order By: Relevance
“…Previous studies demonstrated sexually dimorphic regulation of dopaminergic signaling in the hypothalamus and pituitary of both mammals and fish (Goebrecht et al, 2014;Saha et al, 2015;Scott et al, 2015). Although androgenic steroids regulate dopamine receptor expression in the fish POA (Pasqualini et al, 2009), there are, to our knowledge, no studies testing for sex-specific differences in dopamine receptor-mediated inhibition of POA neural activity.…”
Section: D2r-mediated Inhibition Of Gnrh1 Neurons Is Not Sexually Dimmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies demonstrated sexually dimorphic regulation of dopaminergic signaling in the hypothalamus and pituitary of both mammals and fish (Goebrecht et al, 2014;Saha et al, 2015;Scott et al, 2015). Although androgenic steroids regulate dopamine receptor expression in the fish POA (Pasqualini et al, 2009), there are, to our knowledge, no studies testing for sex-specific differences in dopamine receptor-mediated inhibition of POA neural activity.…”
Section: D2r-mediated Inhibition Of Gnrh1 Neurons Is Not Sexually Dimmentioning
confidence: 86%
“…These results show that the inhibitory mechanisms postsynaptic to dopamine release onto POA GnRH1 neurons are not sexually dimorphic. However, presynaptic dopamine production or release could vary by sex; sexually dimorphic TH expression, as has been observed in fish and mammals (Saha et al, 2015;Scott et al, 2015), could result in sexually dimorphic regulation of dopaminergic control of reproductive behaviors (Goebrecht et al, 2014).…”
Section: D2r-mediated Inhibition Of Gnrh1 Neurons Is Not Sexually Dimmentioning
confidence: 99%
“…This might be mediated by prolactin itself but also by the closely related placental lactogens that act on the Prlr and are elevated in the blood throughout the second half of pregnancy (25). Importantly, unlike some recent reports that have used cell ablation approaches (26,27) or blockade of neurotransmitter production (28,29) to identify critical cell types mediating maternal behavior, in this model, the neuronal circuitry is completely intact. The profound deficit arises specifically from the lack of appropriate hormonal input into these circuits.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of monogamous and promiscuous voles defined a prominent role for the vasopressin and oxytocin pathways in affiliative behaviours, showing, for example, that differences in the spatial distribution of the vasopressin 1a receptor in the male brain are associated with changes in pair-bonding behaviour 2,3 . Oxytocin and vasopressin are known to regulate many aspects of parental care 4–7 , but how genetic variation in these pathways contributes to natural differences in parental care is poorly understood.…”
Section: Introductionmentioning
confidence: 99%